2011
DOI: 10.1007/s11746-011-1877-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varietal Differences on Composition and Thermal Characteristics of Avocado Oil

Abstract: A study was carried out to compare the characteristics of oils from three Malaysian avocado (Persea americana) cultivars with those of the oil from the Australian Hass avocado variety. Oil samples extracted from matured-avocado fruits were assessed for basic physico-chemical parameters, fatty acid and triacylglycerol (TAG) compositions, and melting and solidification characteristics. In comparison to Hass variety, the oil contents of the local avocado cultivars were significantly lower and found to be mostly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 11 publications
6
46
1
3
Order By: Relevance
“…Also the triglyceride profile of avocado oil can be distinctly different from various cultivars. For example, the dominant triglyceride of avocado located in Malaysia were POO, followed by POL, OOO and PPO, while major triglyceride of Hass avocado variety imported from Australian were OOO, followed by POO, OOL and POL 9 . The triglyceride composition may vary by extraction methods.…”
Section: Chemical Composition Of Avocado Oilmentioning
confidence: 99%
“…Also the triglyceride profile of avocado oil can be distinctly different from various cultivars. For example, the dominant triglyceride of avocado located in Malaysia were POO, followed by POL, OOO and PPO, while major triglyceride of Hass avocado variety imported from Australian were OOO, followed by POO, OOL and POL 9 . The triglyceride composition may vary by extraction methods.…”
Section: Chemical Composition Of Avocado Oilmentioning
confidence: 99%
“…[11][12][13][14][15] In addition, the physicochemical characteristics of avocado oils have been evaluated in several countries. [14,[16][17][18][19][20][21][22] Indriyani [23] analyzed the physicochemical properties of different varieties of Indonesian avocado oils (Bantul, Purwokerto, and Garut). However, the Indonesian government does not highlight the production of these avocado varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Puede verse en todas las muestras analizadas, el ácido oleico es el ácido monoisaturado mayoritario en el aguacate. Se ha reportado que el ácido oleico es el ácido graso predominante en aguacate 'Hass' cultivado en Australia, Malasia (Yanty et al, 2011) y Colombia (Pedro y Velásquez, 2015).Sin embargo, la presencia de ácido oleico en forma mayoritaria no es el único factor deseable desde el punto de vista de la salud. Se ha demostrado que entre mayor sea la relación oleico/linoleico (O/L) en el aceite de aguacate, es mejor para la salud, en particular a problemas cardiovasculares (Hwang et al, 1997).…”
Section: Fatty Acidsunclassified
“…It can be seen that in all samples analyzed, oleic acid is the predominant monoisaturated acid in avocado. It has been reported that oleic acid is the predominant fatty acid in avocado 'Hass' grown in Australia, Malaysia (Yanty et al, 2011) andColombia (Pedro andVelásquez, 2015).However, the presence of oleic acid in the majority form is not the only factor desirable from the point of view of health. It has been shown that the greater the oleic/linoleic (O/L) ratio in avocado oil, the better the effect on health, particularly on cardiovascular problems (Hwang et al, 1997).…”
Section: Conclusionesmentioning
confidence: 99%